Claudia Rankine: keynote speaker, Diversity Symposium 2020 - Rankine, Claudia, speaker (Colorado State University. Libraries, 2020)
Claudia Rankine, author of Citizen: An American Lyric, the selection for Colorado State University's inaugural Rams Read, will participate as a keynote speaker during this year's virtual Diversity Symposium.
The 20th annual Diversity Symposium at Colorado State University held on October 19-23, 2020 includes over 35 live Zoom presentations, pre-recorded sessions, keynotes and dozens of learning opportunities on issues surrounding immigration, dismantling systems of power, self-care, race and the criminal justice system, mentorship of underrepresented students, whiteness, teaching rhetorical empathy and more. All sessions will be offered in a virtual setting for CSU faculty, staff and students.
Zoom recording.
Accessibility features: Unedited transcript.
To request an edited transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Diversity Symposium 2020; diversity; inclusion; Colorado State University